Effect of a SGLT2 inhibitor on the systemic and intrarenal renin–angiotensin system in subtotally nephrectomized rats - Li, Lei; Konishi, Yoshio; Morikawa, Takashi; Zhang, Yifan; Kitabayashi, Chizuko; Kobara, Hideki; Masaki, Tsutomu; Nakano, Daisuke; Hitomi, Hirofumi; Kobori, Hiroyuki; Nishiyama, Akira (Journal of pharmacological sciences, 2018)
We aimed to examine the effects of a sodium glucose co-transporter 2 (SGLT2) inhibitor on systemic and intrarenal renin–angiotensin system (RAS) in subtotally nephrectomized non-diabetic rats, a model of chronic kidney disease (CKD). Oral administration of the selective SGLT2 inhibitor, TA-1887 (10 mg/kg/day), for 10 weeks induced glycosuria. However, plasma renin activity, plasma angiotensinogen levels, kidney angiotensin II contents and renal injury were not significantly affected by TA-1887. These data indicate that chronic treatment with an SGLT2 inhibitor does not activate the systemic and intrarenal RAS in subjects with non-diabetic CKD.